Nieznany kurier Piusa XII. Analiza postawy katolickiego misjonarza w sowieckim więzieniu i procesu jego rozpracowywania przez NKGB - Adamski, Łukasz (Dzieje Najnowsze, 2016)
An Unknown Courier of Pope Pius XII. An Analysis of the Stance of a Catholic Missionary in a Soviet Prison and the Process of Investigating Him by the NKGB A major part of this article is based on recently rendered available sources from the SBU State Archives in Kyiv and reconstructs the last months in the life of Father Jerzy Moskwa (1910– 1941) — a Jesuit missionary and courier of Pius XIII and Metropolitan Andrzej Szeptycki (Andrey Sheptytsky). Arrested in January 1941 during his trip from the Vatican to Lviv, Father Moskwa was interrogated by the NKGB and invigilated by two co–inmates, whose detailed reports make it possible to expand knowledge about the methods and techniques applied by the Soviet services, the political and missionary plans of the Vatican involving the Soviet Union, and the infiltration of the Church in Eastern Galicia. Moreover, they comprise a study of a confrontation of the stand of a zealous Christian, represented by Father Moskwa, and Soviet mentality represented by Yevhen Hromovenko, former chief of the Intelligence of Soviet Ukraine, whom the Jesuit was converting in the cell to Christianity.